2016
DOI: 10.1152/ajpgi.00239.2016
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin regulates NHE8 protein expression via the ERK1/2 MAPK pathway in DSS-induced colitis mice

Abstract: Previous studies reported that administration of somatostatin (SST) to human patients mitigated their diarrheal symptoms. Octreotide (an analog of SST) treatment in animals resulted in upregulation of sodium/hydrogen exchanger 8 (NHE8). NHE8 is important for water/sodium absorption in the intestine, and loss of NHE8 function results in mucosal injury. Thus we hypothesized that NHE8 expression is inhibited during colitis and that SST treatment during pathological conditions can restore NHE8 expression. Our data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 38 publications
0
37
0
Order By: Relevance
“…This membrane transport is mediated by three antiporters, NHE2, NHE3, and NHE8, with subtle differences in colonic expression pattern. The latter two are inhibited in animal models of IBD, 9 11 as well as in human patients, 11 , 34 , 35 and deletion of NHE3 in mice was sufficient to lead to microbiome changes similar to that observed in human IBD, 22 microbiota-dependent spontaneous colitis, 20 and increased susceptibility to mucosal injury or T-cell mediated colitis. 21 , 26 These observations prompted us to hypothesize that impaired Na + /H + exchange, be it the result of initial subclinical inflammation or infection, lead to microbial dysbiosis, which in turn lowers the inflammatory threshold or otherwise modulates mucosal immune responses.…”
Section: Discussionmentioning
confidence: 88%
“…This membrane transport is mediated by three antiporters, NHE2, NHE3, and NHE8, with subtle differences in colonic expression pattern. The latter two are inhibited in animal models of IBD, 9 11 as well as in human patients, 11 , 34 , 35 and deletion of NHE3 in mice was sufficient to lead to microbiome changes similar to that observed in human IBD, 22 microbiota-dependent spontaneous colitis, 20 and increased susceptibility to mucosal injury or T-cell mediated colitis. 21 , 26 These observations prompted us to hypothesize that impaired Na + /H + exchange, be it the result of initial subclinical inflammation or infection, lead to microbial dysbiosis, which in turn lowers the inflammatory threshold or otherwise modulates mucosal immune responses.…”
Section: Discussionmentioning
confidence: 88%
“…158,159 Indeed, somatostatin agonists are able to increase intestinal tight junctions in models of dextran sulfate sodium (DSS) and Citrobacter rodentium induced colitis 160 and modulate the water and sodium uptake protein NHE8, associated with UC pathology, via MAPK signaling. 161 Neurotensin þ cells are seen to increase in the mouse DSS model and blocking signaling via antagonists increases pathology via a cyclooxygenase (COX)-2 mediated pathway, 162 indicating a protective effect. Indeed, therapeutic use of peptides or agonists has been beneficial in mouse models, GLP-2 can rescue DSS colitis 163 and small intestinal enteritis 164,165 possibly by reducing bacterial translocation, 166 while nanodelivery of GLP-1 is also protective.…”
Section: Inflammatory Bowel Disease-animal Modelsmentioning
confidence: 99%
“…Enteroendocrine cell detection of inflammation/infection via toll-like receptors 74,76,239 and microbiome dysbiosis via microbial metabolites 75,[77][78][79] Alter epithelial absorption/efflux 161,[242][243][244] Increased sIgA 253,282 Increase tight junction function 160,97,249,250 Direct enteroendocrine cytokine release 74,239,240 Influence cytokine and anti-microbial production from enterocytes 241,248 and Paneth cells 102 Increase crypt cell proliferation via increased growth factor release from myofibroblast 140,141,251,252 Eosinophil 302…”
Section: Direct Immune Modulationmentioning
confidence: 99%
“…A follow-up study also showed that octreotide treatment stimulates colonic NHE8 expression in colitic mice. Both somatostatin receptor 2 (SSTR2) and somatostatin receptor 5 (SSTR5) were involved in restoring NHE8 expression via their roles in suppressing ERK1/2 phosphorylation (174). …”
Section: Regulation Of the Na+/h+ Exchangers Expressed In The Digestimentioning
confidence: 99%
“…Recently, the expression of NHE8 in human UC patients has also been studied. In active UC patients, the expression of NHE8 protein was significantly reduced by ~55% (174). Similar findings were also observed in TNFα-treated Caco-2 cells, where TNFα treatment at 10 ng/mL reduced NHE8 mRNA expression by 40% (311).…”
Section: Na+/h+ Exchange In Pathological Statesmentioning
confidence: 99%